La falta de una normativa en el código de la niñez y adolescencia que obligue a la parte actora a justificar los valores de pensiones atrasadas, en el juzgado de la familia, mujer, niñez y adolescencia de El Oro en la ciudad de Machala del año 2013. - Palma Bustamante, Shirley Elizabeth (2016)
In our country children and adolescents, are considered by the Constitution of the Republic of Ecuador, as one of the priority groups of the Ecuadorian society, which deserve special protection on the part of the family, is on the same basis that they are recognized as holders of the right to food, in other words, hay are beneficiaries of the provision that in their favor a person who is obliged to give them the necessary for their subsistence.